Pengaruh Latar Belakang Pendidikan dan Pelatihan Terhadap Kinerja Karyawan PT. Bank Muamalat Indonesia - Nasyiatul Faridah; Lailatul Hikmah (JPSDa: Jurnal Perbankan Syariah Darussalam, 2021)
The purpose of this study is 1) to determine the effect of educational background (X1) on employee performance (Y); 2) to determine the effect of training (X2) on employee performance (Y); 3) to determine the effect of educational background (X1) and training (X2) simultaneously on employee performance (Y). The research method is quantitative with the type of survey research. The results of study 1) there is a positive and significant influence of educational background (X1) on employee performance (Y); 2) there is a positive and significant influence of training (X2) on employee performance (Y); 3) there is a positive and significant influence of educational background (X1) and training (X2) simultaneously on employee performance (Y).